Applications of Differential Geometry of Curves in Roads Design - Burlacu Adrian; Mihai Adela (Romanian Journal of Transport Infrastructure, 2023)
An important role in the roads design is played by plane curves, if the road lies on a plane surface and by space curves, if the road can not be embeded in a plane. This article presents some work done in the two and three dimensional roads design, by using the differential geometry methods. A study of a general case for plane roads is given.